Eksistensi Nilai Ketuhanan Dalam Budaya Batak Toba - Johan Pardamean Simanjuntak; Yakobus Ndona (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
This research was conducted with the aim of determining the existence of divine values ​​in Toba Batak culture. This research method is to use a descriptive qualitative method with a literature study approach. This research is intended to find out the extent of the existence of divine values ​​in Toba Batak culture, even though it is known that the Toba Batak people have different religions. In conclusion, the results of this research show that Toba Batak culture still highly upholds divine values, and the presence of God can be experienced through encounters with others and the universe. The Toba Batak people believe that the experience of God is present and realized through the application of daily life. It is at that moment that God is experienced as the foundation and soul of all creatures.